Effects of thermal annealing a glass surface in air - Jang, HK; Whangbo, SW; Choi, YK; Jeong, K; Whang, CN; Wang, CH; Choi, DJ; Lee, S (ELSEVIER SCIENCE BV, 2001)
Glass slides were annealed at a temperature range of 300-600 degreesC for 30 min in air. We investigated the effects of thermal annealing treatments on the chemical composition, and surface roughness of the glass. Metallic sodium concentration at the glass surface was 2.2%, but sodium concentration at the annealed glass surface ranged from 4.3% to 5.5%. The sodium composition at the glass surface was greatly increased at an annealing temperature of 400 degreesC, but the sodium composition at the surface was gradually decreased at T-a greater than or equal to 500 degreesC. This phenomenon may be due to the volatility of the sodium atoms at the glass surface. However, carbon concentration at the glass surface was reduced from 49% at room temperature to 22% at annealing temperature (T-a) of 600 degreesC. Surface morphology of the glass was changed with annealing temperature. The root-mean-square surface roughness of the bare glass was 0.6 nm, but the roughness of the glass annealed at a temperature of 300, 400, 500, and 600 degreesC in air for 30 min was 1.0, 1.8, 2.0, 3.0 nm, respectively. (C) 2001 Elsevier Science B.V. All rights reserved.